Associations of short-term exposure to air pollution with risk of pulmonary space-occupying lesions morbidity based on a time-series study - Xu Zhang; Zijie Pei; Yan Wang; Yaxian Pang; Haiyan Hao; Qingping Liu; Mengqi Wu; Rong Zhang; Helin Zhang (BMC Public Health)
Abstract Background Pulmonary space-occupying lesions are typical chronic pulmonary diseases that contribute significantly to healthcare resource use and impose a large disease burden in China. A time-series ecological trend study was conducted to investigate the associations between environmental factors and hospitalizations for pulmonary space-occupying lesions in North of China from 2014 to 2022. Methods The DLNM was used to quantify the association of environmental factors with lung cancer admissions. The heating-, age-, gender-, malignancy-specific effects were further estimated to identify the susceptible groups. Results During the study period, fluctuations in air pollutants and climate conditions closely mirrored changes in hospitalizations for pulmonary space-occupying lesions. Totally, the distributed lag surface showed clear positive associations between pulmonary tumor hospitalization and PM2.5 (RRlag30: 1.000912; 95%CI: 1.000076, 1.00175), PM10 (RRlag30: 1.002246; 95%CI: 1.000474, 1.004021), SO2 (RRlag30: 1.002714; 95%CI: 1.001071, 1.004414), CO (RRlag30: 1.002231; 95%CI: 1.000592, 1.003873). Additionally, the associations between air pollutants and hospitalizations for pulmonary space-occupying lesions were significantly stronger during the heating season. Population aged 65 or older, females and those diagnosed with malignancies were more vulnerable for the risk of pulmonary space-occupying lesions diseases due to air pollution exposure. Conclusions The present study illustrated risk and burden for pulmonary space-occupying lesions hospitalization associated with air pollution, especially among population aged ≥ 65, or female.